2008
DOI: 10.1890/07-0749.1
|View full text |Cite
|
Sign up to set email alerts
|

Flooding Impacts on Responses of a Riparian Consumer to Cross-Ecosystem Subsidies

Abstract: Landscape-driven processes impact the magnitude and direction of cross-ecosystem resource subsidies, but they may also control consumers' numerical and functional responses by altering habitat availability. We investigated effects of the interaction between habitat availability and subsidy level on populations of a riparian fishing spider, Dolomedes aquaticus, using a flood disturbance gradient in the Waimakariri River catchment, New Zealand. D. aquaticus predominantly eat aquatic prey as they hunt from the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 27 publications
0
66
0
Order By: Relevance
“…However, the abundance of aquatic prey was highest at stable rivers. Spider biomass peaked at the intermediate levels of stability, suggesting the existence of a trade off between habitat quality and subsidy availability (Greenwood and McIntosh, 2008).…”
Section: Flows From Streams To Terrestrial Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the abundance of aquatic prey was highest at stable rivers. Spider biomass peaked at the intermediate levels of stability, suggesting the existence of a trade off between habitat quality and subsidy availability (Greenwood and McIntosh, 2008).…”
Section: Flows From Streams To Terrestrial Areasmentioning
confidence: 99%
“…Disturbance can also interact with flows of subsidies. For instance, Greenwood and McIntosh (2008) demonstrated that flood disturbances positively influenced aspects of habitat quality of a riparian fishing spider-there was a higher proportion of habitat in the more disturbed rivers. However, the abundance of aquatic prey was highest at stable rivers.…”
Section: Flows From Streams To Terrestrial Areasmentioning
confidence: 99%
“…Accordingly, much research attention has focused on how terrestrial environmental features regulate subsidy dispersal and the responses of terrestrial consumers (e.g. forest cover, complexity of ground habitats, availability of terrestrial resources), and on how human activities alter these linkages (Petersen et al 2004;Greenwood and McIntosh 2008;Marczak and Richardson 2008;Stenroth et al 2015). However, both the timing and extent of dispersal by adult aquatic insects are further regulated by their species-specific life history traits (Greenwood and Booker 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such a scenario is expected to be common in natural systems under recurrent perturbation dynamics [15]. For instance, spatial flows of nutrients and detritus from a forest to a lake or a river are greatly affected following a fire due to & 2016 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%